Annular Microfluidic Meta-Atom Fusion-Enabled Broadband Metamaterial Absorber - Peng, Jinpeng; Zhang, Yi; Chen, Zihao; Wen, Qiye; Wang, Shaomeng; Li, Yaoyao; Zhou, Aiwu; Sun, Zhengnan; Mu, Xiaohui; Zhang, Xiaosheng (Nano-Micro Letters, 2026)
Electromagnetic (EM) metamaterial absorbers (MMAs) with broadband absorption are of growing interest for applications such as stealth and EM interference mitigation. In this work, we present a novel 3D-printed MMA based on a fused annular microfluidic meta-atom (FAMMA) architecture, designed for W-band absorption. The FAMMA structure features three kinds of orthogonally fused annual meta-atoms, forming a complex 3D microfluidic meta-atom with intricate architecture. Fabricated via high-precision micro 3D printing technology, the FAMMA-based MMA exploits the synergistic solid–liquid coupling effect of the unique three-dimensional orthogonal structure to achieve strong broadband absorption. Three representative FAMMAs with different geometric dimensions have achieved ultra-low reflection loss (RL of − 42.1 dB), ultra-broadband effective absorption bandwidth (EAB of 31.3 GHz), and dual-band absorption (in 76.0–85.3 and 99.1–105.6 GHz), respectively. The underlying absorption mechanisms are elucidated by impedance matching theory and electromagnetic field distribution analyses. Application demonstrations show that the FAMMA-based MMA significantly suppresses radar echo power and renders metallic targets undetectable to both radar detector and radar imaging systems, highlighting its potential in stealth technology. Overall, this work establishes a new design concept for high-performance broadband millimeter wave MMAs, opening new avenue for future applications such as high-speed communication, through-wall sensing, and drone detection. Highlights: 1 Unique 3D-printed electromagnetic metamaterial absorber based on a fused annular microfluidic meta-atom architecture. 2 Synergistic solid-liquid coupling effect of the unique three-dimensional orthogonal structure to achieve strong broadband absorption. 3 High-performance broadband absorption for millimeter wave.